Analisis Profitabilitas Terhadap Kinerja Keuangan Pada PT Midi Utama Indonesia Tbk - Yulita, Elvin; Alimuddin, Alimuddin (Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
This study aims to evaluate the financial performance of PT Midi Utama Indonesia Tbk. Profitability ratios are used to measure the effectiveness of company management in generating profits. The data for this study uses secondary data, namely the financial statements of PT Midi Utama Indonesia Tbk for the period 2020 to 2022. Data analysis using profitability ratios. The analysis results show an increase in the company's financial performance from 2020 to 2022, with an increase in GPM, NPM, ROA, and ROE. This shows the company's ability to generate better profits from year to year. PT Midi Utama Indonesia Tbk has shown an increase in gross profit margin, net profit margin, return on assets, and return on equity from 2020 to 2022, indicating good financial performance.